Pharmacokinetics of the combination raltegravir/atazanavir in HIV‐1‐infected patients1. Issue 7 (18th March 2013) - Jansen, A; Colbers, EPH; van der, AJAM; Richter, C; Rockstroh, JK; Wasmuth, JC; van, M; Burger, DM
<x xml:space="preserve">Abstract</x> Objectives To evaluate the use of raltegravir with unboosted atazanavir in combination with one nucleoside reverse transcriptase inhibitor (NRTI) (lamivudine or emtricitabine) as a potentially well‐tolerated once‐daily (qd) maintenance regimen. Methods We compared the pharmacokinetics of raltegravir 400 mg twice daily (bid) with raltegravir 800 mg qd in HIV‐infected patients (n = 17) on unboosted atazanavir (600 mg qd) in combination with lamivudine or emtricitabine. Results The area under the plasma concentration vs. time curve for a dose interval t (AUC0–t) of 800 mg qd divided by 2 was not significantly different from the AUC0–t of 400 mg bid (P = 0.664) but the minimum concentration (Cmin) was 72% lower with the qd regimen (P = 0.002). The regimen was well tolerated and the viral load remained undetectable in all patients during the 6 weeks of the study follow‐up. Conclusions A qd regimen of raltegravir 800 mg, atazanavir 600 mg and lamivudine or emtricitabine resulted in favourable pharmacokinetic profiles and good short‐term safety and efficacy data. Larger phase IIb studies are needed to explore this novel regimen.